A influência da pandemia de COVID-19 na saúde mental de estudantes universitários, uma visão da terapia ocupacional: revisão sistemática da literatura - BORGES, Thayro Matheus Reis (2023)
COVID-19 is a disease caused by the Sars-Cov-2 virus that has become a serious global health problem, spreading to several countries in the world, configuring itself as a pandemic. The daily routine started to be structured based on the reduction of social contact and other forms of prevention, thus molding a routine that is unusual for individuals, in various sectors of society, including higher education. The objective was to analyze the studies that address the mental health of university students during the COVID-19 pandemic period, relating to Occupational Therapy and the possible impacts on occupations. Therefore, it is a study of systematic literature review in the databases PubMed Central (PMC), Publisher of Open Access Journals (MDPI) and Journal of Medical Internet Research (JMIR), using the descriptors “university students” and “Mental health” and “COVID-19” and “occupational therapy”. Full and free original articles, in Portuguese or English, published in the last 5 years will be included; from January 2015 to December 2020. The results of this research emphasize the prevalence of depression and anxiety among university students during the COVID-19 pandemic period, thus affecting their mental health, and also that it is necessary to develop more research on the subject, involving Therapy Occupational.